Using social media to navigate changing rural markets: the case of small community retail and service businesses. (2nd November 2021) - Son, Jihyeong; Niehm, Linda S.
Abstract: To help small firms navigate changing rural markets, this study investigated how small businesses use social media to expand their customer and stakeholder networks to sustain their businesses. Focus group interviews with owners of small retail and service businesses were conducted in three selected rural Iowa communities. Our findings indicate that social media is an innovative marketing tool to promote interactive, collaborative, and personalized interactions with customers and stakeholders. These interactions enabled small businesses to attract new customers and foster commitment to the business. In addition, reciprocal relationships with stakeholders leveraged social media content creation and fostered social capital formation. However, social media integration poses challenges for many small businesses, due to operational, economic, infrastructural, legal and regulatory, and psychological factors. Our findings highlight education, legal and regulatory guidelines and policies, tools to measure the effectiveness of social media on marketing, and business assistance and support for small businesses to utilize social media to build customer and other business support networks. Implications support the potential for social media to enhance online interactions for these small firms, leading to the development of social capital, a valuable source of competitive advantage and business sustainability in rural markets.